(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
Purpose: Green HR hos a vital role in restructuring & reengineering the business to environmental friendly business where the priorities have been shifted to be a green economy. Green HR emphasizes on the contribution of people management policies and practices towards the brooder corporate environmental agenda. Green HR activities Comprises of video recruiting to minimize travel requirements and minimizing the amount of printed materials used in performance appraisals and other HR activities, use of environment friendly Green machines at workplace like bicycles This study reflects how green HR is addressing environmental issues and various green HR methodologies that con be adopted to achieve a green business. Analysis of Green HRM as a high performing system, that review role of HR in business by minimizing the wastage and incurred cost . In nutshell, the effectiveness of Green HR leads to optimizing the use of resources. Design/ methodology/Approach: It is a case based research in which the companies following Green HRM practices have been studied. The green HRM Practices hos drown an outstanding success in UK and in China. Findings: As it is a case based study and case studies of many International companies hove been studied and analyzed to study how these organizations hove addressed environmental issues in their business. And what methodologies they hove adopted to be a port of green business and how they hove minimized the organizational wastages. Research limitations/implications: The accuracy of the analysis is totally dependent on the authenticity of the coses which hove been referred in the research to study the Green HRM roles in business and Green HRM methodologies. Practical implications: During the recession Green HRM with a huge environmental focus ployed a vital role in reducing waste and optimizing resources. These Green HRM practices con be adopted in Indian context and thus contribute to the brooder corporate environmental agenda by taking Green Management Initiatives like going paperless, reduce commuting, reducing business travel, buying green, detoxifying etc. Green HR is a new dimension of traditional HR which is required to be explored and worked upon. This study also provides opportunity to academics to further establish theories and coses. Originality/value: This research paper is on honest attempt to addresses green environmental issues with context to HRM and green HRM Methodologies and also studies role of green HRM in post- recession and minimizing its effect.